As representações sociais sobre trabalho de trabalhadoras da limpeza de empresa terceirizada em universidade pública - Roldão, João Marcos Leão (Universidade Federal de São Carlos, 2022)
The present research sought to understand, considering the centrality of human labour for the psyche and the phenomenon of the precariousness of contemporary working conditions, the contents and psychosocial strategies that constitute the social representations about the work of workwoman who provide services to an outsourced cleaning company within a university campus. In order to do so, we analyzed their occupation trajectories, sociodemographic categories, collective identities, interpersonal relationships and, above all, their understanding of the contradictions lodged in their productive activities. After conducting semi-structured interviews and the subsequent confrontation of the reports with critical theoretical- methodological references, we were able to have access to a myriad of meanings related to a complex work reality. Such social representations revealed the dialectic relations of oppression and emancipation, of empathy and hostility, of companionship and invisibility, of solidarity and competitiveness that coexisted within the outsourced cleaning job and, above all, in the subjective constitution of the precariat.
Social representations about the work of outsourced cleaning workers at a public university
Keywords: Representações sociais; Trabalhadores terceirizados; Precarização do trabalho; Universidade pública; Precariado; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO TRABALHO E ORGANIZACIONAL